Passé et avenir du théâtre de science-fiction - Susan Gray; Christos Callow Jr. (ReS Futurae, 2021)
The article focuses on the past history and future developments of science fiction theatre. It reports that science fiction theatre has existed unofficially since the 19th century and discusses several theatrical plays including R.U.R, Back to Methuselah, and Endgame. It further mentions that science fiction theatre concerns with the impact of technology on our lives and is also capable of providing importance to theatre and science fictional culture in future.